Exploring the Influence of Principal Leadership and Self-Development on Teacher Competence: Does the Mediation of Self-Experience Matter? - Faradila, Annisa Nur; Wit Daryono, Rihab (Jurnal Pendidikan Islam, 2024)
Purpose – This study aims to examine the influence of principal leadership and self-development on teacher competence, with self-experience serving as a mediating variable. It investigates both direct and indirect relationships to understand how these variables contribute to professional capacity building in education. Design/methods/approach – This research employed a quantitative approach using an ex post facto design. The sample consisted of 58 teachers from two Islamic junior high schools in East Java, selected through purposive sampling. Data were collected using a structured questionnaire covering four variables: principal leadership, self-development, self-experience, and teacher competence. A five-point Likert scale was used, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The evaluation included tests for convergent and discriminant validity, reliability, coefficient of determination (R²), effect size (ƒ²), predictive relevance (Q²), and both direct and indirect path coefficients. Findings – The results show that principal leadership has a significant direct effect on teacher competence (β = 0.468, T = 3.002, p < 0.01), but no significant effect on self-experience (β = –0.066, p > 0.05). Self-development significantly influences self-experience (β = 0.882, T = 5.897, p < 0.001), though its direct effect on teacher competence is not significant (β = 0.197, p > 0.05). Self-experience positively influences teacher competence (β = 0.324) but does not serve as a statistically significant mediator in the relationship between either principal leadership or self-development and teacher competence. The model explains 81% of the variance in teacher competence (R² = 0.810) and shows strong predictive relevance (Q² = 0.566). Research implications – Fi Schools and educational policymakers should support leadership development and design self-development programs that emphasize reflective practice. Teachers should be encouraged to engage in activities that integrate personal teaching experiences into their professional growth strategies to optimize instructional effectiveness.